A review on antibacterial properties of eucalyptus oil and different eucalyptus species used in pharmaceuticals - Vijay Aadhithya; Nageshwari Raja; Praveena PL; Sreenithi K; Jayashree M (International Journal of Antibiotics, 2024)
Medicinal plants with antimicrobial compounds play a crucial role in combating various pathogens. Eucalyptus, belonging to the myrtle family, is notable for its diverse antimicrobial compounds. This fast-growing plant thrives in many countries and its various parts offer significant medicinal value, including timber, pulpwood, and essential oils. The leaves, often considered forest harvesting waste, contain essential oils with potential medicinal benefits. Members of the genus Eucalyptus are highly valued for their contribution to various commercial essential oils and aroma chemicals. Extracts obtained from these plants undergo thorough analysis, including phytochemical examination, quantitative assessment, and antibacterial assays. In the phytochemical analysis of Eucalyptus oil, key components identified include 1,8-cineole, α-terpinyl acetate, ρ-cymene, and ϒ-terpinene. Eucalyptus oils have demonstrated a pronounced bacteriostatic effect against gram-positive bacteria, while the oil derived from Eucalyptus urophylla hybrid has been observed to specifically affect gram-negative bacteria. These antibacterial properties are associated with the terpenoid content present in the essential oils. Appreciating the antibacterial qualities of essential oils is essential in choosing suitable antibiotics, whether they are bacteriostatic or bactericidal, for effective treatment. The formulations derived from these oils hold promise for potential applications in both the food and pharmaceutical industries. In summary, the study highlights the antimicrobial potential of Eucalyptus essential oils, emphasizing their effectiveness against a range of bacteria. The findings suggest potential applications in various industries, including food and pharmaceuticals
Keywords: Eucalyptus oil; Phytochemicals; antibacterial activity; antioxidants; bacteriostatic; essential oils; natural antibiotics; plant extract